Trends in player body mass at men's and women's Rugby World Cups: a plateau in body mass and differences in emerging rugby nations. Issue 1 (4th January 2021) - Tucker, Ross; Lancaster, Stuart; Davies, Phil; Street, Gary; Starling, Lindsay; de Coning, Cian; Brown, James
Abstract : Objectives: This study assessed the mass of international rugby players in the men's and women's Rugby World Cups between 1991 and 2019. The objective was to quantify changes in mass of players by position, and to compare changes between men and women, and between established (Tier 1 (T1)) and emerging (Tier 2 (T2)) rugby nations. Setting: Rugby World Cups from 1991 to 2019 for men's players and 2010 to 2017 for women's players. Participants: 4447 elite male and 958 elite female players. Primary and secondary outcome measures: Player body mass, grouped as men and women, T1 and T2 nations, and by playing position, assessed over time. Results: Men's player mass increased significantly between 1991 and 2019 (T1 overall 9.7% increase), but this increase occurred almost entirely up to 2011. Women's forwards mass increased by 4.8% in T1, with no changes in T2 or backs from either tier. Significant differences in mass were found between T1 and T2 forwards and backs for both men and women. Conclusions: The body mass of men's players has stabilised after initial increases following professionalisation. Player body mass may be approaching a plateau, beyond which no further performance advantages occur. Changes to laws and tactical approaches by coaches may have contributed to this, by changing match demands on players, necessitating endurance, agility and speed. Trends in the evolution of T2 players suggest a barrier to identifying and developing heavy athletic players, and may require intervention to ensure competitive parity.